ChemInform Abstract: A Versatile Metal‐Free Intermolecular Aminochlorination of Alkenes. Issue 32 (24th July 2014) - Martinez, Claudio; Muniz, Kilian
Abstract The aminochlorination of a variety of alkenes with chloramine‐T produces one of the two possible regioisomers selectively, depending on the reaction conditions used.